Factors influencing the non-disclosure of sustainability information on Malaysian district councils' websites within an institutional theory framework / Corina Joseph - Corina, Joseph (Research Management Institute (RMI), 2011)
This study examined why Malaysian district councils did not report sustainability information on their websites. It is a case study approach using semi-structured interviews. Results indicated that internal and external organizational factors influenced the non-reporting of sustainability information on councils' websites. In institutional theory, the lack of commitment shown by the top management in implementing sustainable development program appears to discourage the promotion of normative isomorphic pressure for disclosing sustainability information on websites. There is evidence of coerciveisomorphism relating to website bureaucratic procedures, but, not relating to disclosure of sustainability information. The overall findings may assist in formulating policiesto encourage district councils to report sustainability information to stakeholders.